Towards a new legal framework for sustainability under the European Green Deal - Jendrośka, Jerzy; REESE, Moritz; SQUINTANI, Lorenzo (The Opole Studies in Administration and Law, 2021)
The European Green Deal is a comprehensive initiative aimed at reshaping the functioning of the European Union towards sustainable development. While the immediate trigger for this initiative of the newly appointed European Commission under Ursula van Leyen was the need to address the challenges associated with climate change and to move towards carbon-free and circular economy – its goals seem to be much more ambitious: to put into practice the concept of sustainable development. Against the background of the concept of sustainability and its various ambiguities and interpretations, the article provides a brief description and analysis of the key pillars of the Green Deal, namely: the financial framework for promoting sustainability, the climate and energy strategy, and the strategy for industry and circular economy. It also presents and critically assesses the horizontal goals of the Green Deal i.e. improving involvement of the public into the decision-making and assuring equal opportunities for marginalised groups.